A Feedback Regulatory Loop Involving dTrbd/dTak1 in Controlling IMD Signaling in Drosophila Melanogaster - Hua, Yongzhi; Zhu, Yangyang; Hu, Yixuan; Kong, Fanrui; Duan, Renjie; Zhang, Chao; Zhang, Chuchu; Zhang, Shikun; Jin, Yiheng; Ye, Yizhu; Cai, Qingshuang; Ji, Shanming (Frontiers in Immunology, 2022)
Negative regulators of the inflammatory responses are essential for the maintenance of immune homeostasis and organismal fitness. In Drosophila, the deubiquitinase (Dub) dTrbd selectively restricts the K63-linked ubiquitination modification of dTak1, a pivotal kinase of the IMD signaling pathway, to regulate the IMD innate immune response. However, which domain and how it functions to enable dTrbd’s activity remain unexplored. Here, we provide compelling evidence showing that the NZF domain of dTrbd is essential for its association with dTak1. Meanwhile, the Linker region of dTrbd is involved in modulating its condensation, a functional state representing the Dub enzymatical activity of dTrbd. Of interest, the activated IMD signals following bacterial stimuli enhance the dTrbd/dTak1 interaction, as well as the condensate assembly and Dub enzymatical activity of dTrbd. Collectively, our studies shed light on the dual mechanisms by which the IMD signaling-mediated feedback loop of dTrbd/dTak1 precisely regulates the innate immune response in Drosophila.